FORMATION OF COMMUNICATIVE COMPETENCE OF FUTURE DOCTORS OF PHILOSOPHY IN THE CONDITIONS OF POSTGRADUATE STUDIES - Volkova Nataliia Pavlivna; Lebid Olha Valeriivna (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article is devoted to the formation of communicative competence. It considers the importance of communicative competence in the content and structure of professional training of future doctors of philosophy in the specialty 015 “Vocational Education (by specializations)” in graduate school. The commu- The communicative competence of a teacher of higher education is considered by the authors as an integral personal education that ensures the effectiveness of communication in the system of professional relations and provides a conscious understanding of the value of communication for professional activities, mastery of culture and communication technologies, verbal, nonverbal and computer communication, updating one’s own communicative experience. The structural components of a certain competence are characterized: motivational-value (set of motives, adequate to the goals and objectives of communicative activity (motivation for communicative activity, focus on humanistic communication, the need for communicative self-improvement)); cognitive (a set of knowledge about the nature and features of communication in general and professional, in particular, fields, knowledge about communication styles, in particular, about the features of one’s own communicative style); activity (set of communicative skills (organizationalmanagerial, perceptual-reflexive, expressive)); personal-emotional (a set of personal qualities that determine the position and orientation of graduate students as subjects of communicative activity, as well as the emotional manifestation of these qualities (ability to reflect, empathy, contact, observation, stress resistance)). The principles (contextual learning, communicative interaction, individual support by the teacher of educational activities of each postgraduate student, internal freedom of a person, joint activities of subjects of the educational process and reliance on experience of the student, critical self-assessment) and pedagogical conditions of formation of communicative competence of future doctors of philosophy are substantiated. conditions of postgraduate study (achievement of communicative orientation in teaching all disciplines provided by the curriculum of third (educational) level) in stimulating postgraduate students to acquire communicative competence, ensuring their self-realization in various communications, creating an atmosphere of partnership between teachers and graduate students interactive learning technologies). The article describes and analyzes the results of experimental verification of the effectiveness of the application of pedagogical conditions for the formation of communicative competence of future doctors of philosophy in graduate schools. The conclusion about the efficiency of application of certain pedagogical conditions and expediency of their introduction into the process of professional training of future doctors of philosophy studying in the educational-scientific program “Professional education” (specialty 015 “Professional Education (by specializations)”) is made